2004
DOI: 10.1097/01.ju.0000135368.77589.7c
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Enhanced Spiral Computerized Tomography in Patients With Chronic Obstructive Uropathy and Normal Serum Creatinine: A Single Session for Anatomical and Functional Assessment

Abstract: Contrast enhanced spiral CT is more sensitive than IVP for identifying the cause of chronic obstructive uropathy. Moreover, it is as accurate as radioisotope renal scan for calculating the total and separate kidney function. We recommend spiral CT with contrast medium as a single radiological diagnostic modality for the assessment of patients with chronic renal obstruction and normal serum creatinine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…Evidence has shown the differential renal parenchyma volume measured by noncontrast CT provides a fairly accurate prediction of differential creatinine clearance (7). El-Dein et al demonstrated that contrast enhanced spiral CT is as accurate as nuclear renography for calculating total and separate renal function (8). There are, however, major drawbacks to these forms of renal function estimation.…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has shown the differential renal parenchyma volume measured by noncontrast CT provides a fairly accurate prediction of differential creatinine clearance (7). El-Dein et al demonstrated that contrast enhanced spiral CT is as accurate as nuclear renography for calculating total and separate renal function (8). There are, however, major drawbacks to these forms of renal function estimation.…”
Section: Commentsmentioning
confidence: 99%
“…There are, however, major drawbacks to these forms of renal function estimation. Primarily, these studies required sophisticated software to calculate total renal volume based on CT reconstructions (8). Such scans must be performed as a dedicated study as data from existing scans may not be adequate for the sophisticated reconstructions and volume rendering required.…”
Section: Commentsmentioning
confidence: 99%
“…Müller-Lisse et al found in 26 patients that urothelial cancer can often be diagnosed or ruled out by MSCT without the need for an excretory phase [50]. Moreover, the cause of obstruction is often diagnosed on nephrographic-phase CT scans obviating excretory-phase imaging [51]. On the other hand, it is plausible that especially the diagnosis of subtle non-occluding or slightly obstructing urothelial lesions requires the best possible opacification of the entire urinary tract.…”
Section: Discussionmentioning
confidence: 99%
“…This results in a small reduction in radiation exposure to the patient, reduced utilisation of imaging resources, and a more convenient assessment algorithm for the potential donor [44][45][46]. However, most analyses were based on correlation with significance testing of the differences between the two methods and so cannot provide a meaningful assessment [39].…”
Section: Discussionmentioning
confidence: 99%